Peace Education and Conflict Prevention in Somalia - Mohamed, Abdiwahid Hussein (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
This study focused on Peace Education and Conflict Prevention in Somalia. The specific objectives of the study were to find out the different perceptions of the Somali people on peace education and conflict prevention in Somalia, to explore the importance of peace education in conflict prevention in Somalia and to determine the relationship between peace education and conflict prevention in Somalia. The study used qualitative research design using documentary analysis of various perspectives of the Somali people and that of scholars. The goal of the researcher was to expose the perspective of Somali educators on the importance of peace education and the possible causes and consequences of the conflict as well as the relationship that exist between peace education and conflict in Somalia. This study carried out a critical review of existing literature with in-depth interviews with key informants from the education sector. By employing qualitative approach in the study, the researcher carried out a thorough investigation into a wide range of secondary. Data was collected via the use of documentary review and interview guide. The study also relied on secondary data from textbooks, journals, and academic papers. The main findings of the study revealed that that peace education contributes to conflict prevention in Somalia. This was clearly revealed from the finding of the study where majority of the respondents an overwhelming majority of over (90%) of the participants in the study showed positive and relevant perception about peace education being the best tool that can be used to prevent conflict in Somalia, the study revealed that (100%) of the participants in the study agreed that peace education is vastly important in as far as conflict prevention is concerned in Somalia and lastly the study revealed that (100%) of the participants agreed and noted that peace education is related to conflict prevention. The study recommends that the Ministry of Education of the Federal Republic of Somalia and should reform and revise the current secondary and primary schools curriculum and then incorporate peace education with all the required contents which are instrumental in providing in-depth knowledge and skills to prevent conflict in Somalia, the Ministry of Education of Somalia should review the structure of the peace education programme goals, and its organization in order to bear fruits it is prepared for. Teachers, students, and parents are not familiar with the target goals and structure of peace education in Somalia. It is in this context that the program is still unpopular among these groups of people and the Federal Government of Somalia should ensure proper and timely training of teachers on peace education.